Efficacy and safety of obinutuzumab in primary membranous nephropathy: a real-world retrospective study - Xi Cheng; Zhen-feng Zheng; Yan Qi; Xin Cao; Xi-qian Gao; Ying-xin Fang; Li Wei; Wen-ya Shang; Tie-kun Yan; Jun-ya Jia; Peng-cheng Xu; Qiu-hua Gu (Frontiers in Immunology)
ObjectiveThis study aimed to evaluate the efficacy and safety of obinutuzumab, a novel anti-CD20 monoclonal antibody, in patients with primary membranous nephropathy (pMN).MethodsFifty-five patients with pMN treated with obinutuzumab were respectively enrolled in this study. Clinical and immunological response, renal function and adverse events were assessed throughout the follow-up period between patients receiving obinutuzumab as initial therapy and alternative therapy.ResultsThe study included 40 patients receiving obinutuzumab as an alternative therapy, and 15 patients receiving it as an initial therapy. During a follow up of 13.0(10.0, 18.0) months after obinutuzumab treatment, 23/25(92.0%) patients achieved immunological remission. 46/55(83.6%) patients achieved clinical remission (including 40.0% of PR and 43.6% of CR), with significantly reduced proteinuria and increased serum albumin. Patients with obinutuzumab as either the initial or alternative treatment showed similar clinical response (85.0 vs. 80.0%, P=0.692). 13 out of 18 patients (72.2%) with impaired kidney function (eGFR <60 mL/min/1.73 m²) also showed significant response to obinutuzumab, along with eGFR increasing from 35.3 to 47.6 mL/min/1.73m². Furthermore, obinutuzumab also had a comparable efficiency in patients without response to previous rituximab treatment and patients with negative anti-PLA2R antibody. More patients in the initial therapy group had infusion-related reactions (33.3 vs. 15.0%, P=0.149), while severe infections were all occurred in the alternative therapy group, particularly those with a history of long-term immunosuppressive therapy.ConclusionsObinutuzumab, used as both initial and alternative therapy, can induce significant clinical response in patients with pMN, implying its potentially promising therapeutic effect on pMN.